Social Impact Analysis of Stunting Prevention Programs Is Important Using the Social Return of Investment (SROI) Study Method - Bernadi, Agustya Hendy; Amalia, Dinne Shovia Tresna; Latif, Agusman Muhammad (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the social impact of the Prevent Stunting Is Important Program implemented by PT BRI (Persero) Tbk through the Social Return on Investment (SROI) approach. This program is part of the company’s Social and Environmental Responsibility (TJSL) initiative implemented in 24 Community Health Centers (Puskesmas) in 17 Cities/Regencies in Indonesia. The research method uses an evaluative SROI analysis with data collection through in-depth interviews, Focus Group Discussions (FGDs), and secondary data review. The results show that every Rp 1 invested generates a social benefit value of Rp 1.37 during the period from November 2023 to November 2024. The largest distribution of benefits is received by the community (67.09%), followed by the government (27.69%), and the company (5.22%). This program contributed to a decrease in stunting prevalence by 0.09% with a rate of change reaching 7.98% post-intervention. This study recommends expanding stakeholder engagement, a long-term comprehensive approach, optimizing PMT provision, and adding an economic empowerment component for parents of stunted children to increase program effectiveness.